Structural optimization of solar chimney system based on heat efficiency and flow velocity: Numerical and Experimental studies - Jing Jia; Jing Nie; Hao Su; Jin-Chen XU; Xinyao Ruan; Wei Gao (Case Studies in Thermal Engineering)
This study focuses on enhancing the heat collection performance of solar chimney systems (SCS). The effect of various sizing parameters on the square SCS with a single side inlet is investigated through experimental and numerical simulations for optimization. The experimental results demonstrate significant variation in temperature uniformity among absorbers made from different materials. The composite absorber consisting of bamboo glue board, aluminum, sand, and black high-density polyethylene foam board exhibits excellent temperature uniformity. Optimization is performed with heat collection efficiency and chimney inlet fluid velocity as objective functions. The results indicate that adjusting the transparent cover inclination angle and chimney dispersion angle significantly enhances heat collection efficiency. Specifically, the SCS achieves a heat collection efficiency of 42.54 % when the inclination angle is set to 10° and the chimney dispersion angle is set to 1°. The chimney inlet fluid velocity of the SCS varies with different chimney dispersion angles at the same transparent cover inclination. At a dispersion angle of 2°, the velocity reaches a maximum of 2.090 m/s. Due to the large transparent cover area of the SCS, it is recommended to integrate the SCS with buildings and agriculture to achieve zero energy consumption and promote sustainable agriculture.